Distribution and species composition of potato viruses in the Novosibirsk region - V. S. Maslennikova; M. B. Pykhtina; K. A. Tabanyukhov; E. V. Shelikhova; K. I. Mosalev; A. V. Katokhin; A. A. Bondar; A. B. Beklemishev; M. I. Voevoda (Вавиловский журнал генетики и селекции)
Among the many diseases that aﬀect potato plants, viral infections are the most common and cause significant damage to farms, aﬀecting both the yield and quality of potatoes. In this regard, an important condition for preserving the potato seed fund in Russia is systematic monitoring and early highly specific detection of potato viral infections. The purpose of the work is to study samples of potato varieties collected in the Novosibirsk region for the presence of viral infections using RT-PCR. 130 potato plants from three districts of the Novosibirsk region (NR) were studied. As a result of monitoring, the following viruses were identified: PVY (potato virus Y), PVS (potato virus S), PVM (potato virus M) and PVX (potato virus X). The quarantine pathogen potato spindle tuber viroid (PSTVd) was not detected in any of the samples analyzed. The maximum frequency of occurrence in the region was noted for three viruses: PVY, PVM and PVS. A significant proportion of the samples were mixed viral infections: the occurrence of the combination of infection PVY + PVM in plants was 25.0 %, and PVY + PVS, 22.6 %. To develop methods for determining the strain affiliation of the studied samples, the nucleotide sequences of the capsid protein genes of 10 Y-virus isolates were sequenced. Phylogenetic analysis of the studied sequences of NR isolates was carried out with a set of sequences of reference strains 261-4, Eu-N, N:O, NE-11, NTNa, NTNb, N-Wi, O, O5, SYR_I, SYR_II and SYR_III retrieved from GenBank. As a result of phylogenetic analysis, it was established that NR viral samples fell into two groups of strains: group 1, which also includes isolates of the reference strains 261-4/SYR_III, and group 2, NTNa. The obtained results of the strain affiliation of NR samples lay the basis for the development of DNA and immunodiagnostic systems for identifying PVY circulating in NR, as well as for elucidating the source and routes of entry of specific virus strains.